2015
DOI: 10.1080/13607863.2015.1124836
|View full text |Cite
|
Sign up to set email alerts
|

What are the essential features of resilience for informal caregivers of people living with dementia? A Delphi consensus examination

Abstract: The essential elements of resilience selected from multiple stakeholder perspectives can be used to select appropriate outcomes for intervention studies and give guidance to policy to support caregivers more effectively and better tailored to their needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 36 publications
6
51
0
Order By: Relevance
“…In addition, the observation that caregivers tend to fall back on emotion and avoidance-style coping strategies as cognitive problems increase should be further studied. Resilient caregivers of patients with dementia were found to have a better outlook; higher quality relationship with the care recipient; and well-informed, adequately supported, and appropriate users of healthcare resources [53].…”
Section: Cognitive Impairment and Caregiver Resiliencementioning
confidence: 99%
“…In addition, the observation that caregivers tend to fall back on emotion and avoidance-style coping strategies as cognitive problems increase should be further studied. Resilient caregivers of patients with dementia were found to have a better outlook; higher quality relationship with the care recipient; and well-informed, adequately supported, and appropriate users of healthcare resources [53].…”
Section: Cognitive Impairment and Caregiver Resiliencementioning
confidence: 99%
“…The actual concept of resilience has evolved as the scientific knowledge about it has increased, but there is still no consensus on an operational definition (Herrman et al, 2011). experiencing positive aspects of caregiving, and a good quality of life of caregivers were also included in the term (Joling et al, 2017). This shows that the resilience concept is not a standardized concept, but is constantly evolving.…”
Section: The Role and Influence Of Day Care As A Community Resourcementioning
confidence: 99%
“…A study which sought to obtain a carer‐derived definition of resilience found participants had such difficulty with the question it was dropped from the interview schedule and a definition was supplied by the researcher (O'Dwyer, Moyle, Taylor, Creese, & Zimmer‐Gembeck, ). An earlier study aiming to define resilience used a Delphi process (Joling et al, ) and included family carers but the statements which informed the process were again derived by the research team. The current study enables carers to share their own insights.…”
Section: Introductionmentioning
confidence: 99%